Income tax buyouts and income tax evasion - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2014)
A tax buyout is a contract between tax authorities and a tax payer which reduces the marginal income tax rate in exchange for a lump-sum payment. While previous contributions have focussed on labour supply, we consider the interaction with tax evasion and show that a buyout can increase expected tax revenues. This will be the case if (1) the audit probability is constant and the penalty for evasion is a function of undeclared income or (2) the penalty depends on the amount of taxes evaded, and authorities use information about income generated by the decision about a tax buyout offer when setting audit probabilities. Since individuals will only utilise a tax buyout if they are better off, higher tax revenues imply that such contracts can be Pareto-improving.
Keywords: D82; H21; H24; H26; 330; Asymmetric information; Revenues; Self-selection; Tax buyouts; Tax evasion